2009
DOI: 10.1007/s11999-009-0788-8
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Locked Pubic Symphysis: An Open Reduction Technique

Abstract: A locked pubic symphysis occasionally occurs after a lateral compression injury of the pelvic ring. One pubic bone becomes entrapped behind the contralateral pubis. Lateral compression pelvic injuries are well recognized, but a lateral compression pelvic injury resulting in a locked pubic symphysis is rare. We describe a locked pubic symphysis with greater than 4 cm overlap that was reduced with simple maneuvers and readily available instruments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 12 publications
0
19
0
2
Order By: Relevance
“…Previously described open reduction techniques include direct traction of the incarcerated ODPS with reduction forceps, releasing the trapped pubic tubercle with a ball-spike reduction tool and mallet, and levering the ODPS with a blunt Hohmann retractor 11 . No reports in the literature have favored one technique over another.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously described open reduction techniques include direct traction of the incarcerated ODPS with reduction forceps, releasing the trapped pubic tubercle with a ball-spike reduction tool and mallet, and levering the ODPS with a blunt Hohmann retractor 11 . No reports in the literature have favored one technique over another.…”
Section: Discussionmentioning
confidence: 99%
“…Previous case reports have described scenarios during which the pubis becomes entrapped within the obturator foramen as it punctures through the obturator membrane4,6,7,11 . There are few reports that support attempts at closed reduction; others suggest reduction in the operating room, followed by fixation.…”
mentioning
confidence: 99%
“…However this maneuver has the risk of causing fracture in the femoral neck. It is reported that reduction may be provided by stabilizing the opposite iliac bone and using the femur as a lever in Figure 4 [7] or by applying longitudinal traction to the affected lower extremity; [6,8] by applying lateral compression while pressing directly on the symphysis pubis; [2,4] or by pressing on the symphysis pubis while distracting bilaterally over both iliac crests. [3] Botanlıoğlu et al [9] reported that after lateral compression provided by an external fixator placed on both iliac crests, open reduction could be obtained by force applied from the anterior to the posterior with an elevator as a convex surface directed towards the pelvis placed between the pubic bone and opposite the pubic tubercle through the obturator foramen.…”
Section: Discussionmentioning
confidence: 99%
“…Presentano frequenti rischi lesionali nel maschio (uretra, prostata, plesso venoso prostatico); con una certa frequenza esitano in insufficienza erettile. In letteratura esistono molti case report al riguardo [9][10][11][12][13][14][15]. Maqungo propone una classificazione in tre gradi di gravità crescente; il 2°e il 3°grado richiedono sempre un trattamento chirurgico.…”
Section: Fig 2 -Lussazioni Della Sinfisi: In Apertura E In Chiusuraunclassified
“…Maqungo propone una classificazione in tre gradi di gravità crescente; il 2°e il 3°grado richiedono sempre un trattamento chirurgico. Sono lussazioni tipiche dei maschi perché, come suggerito da Cannada e Reinert [12], la sinfisi delle donne ha un disco più spesso e una mobilità maggiore. Il trattamento è chirurgico, con accesso di Pfannestiel e osteosintesi interna.…”
Section: Fig 2 -Lussazioni Della Sinfisi: In Apertura E In Chiusuraunclassified